SDSS-IV MaNGA: local and global chemical abundance patterns in early-type galaxies. Issue 3 (7th December 2018) - Parikh, Taniya; Thomas, Daniel; Maraston, Claudia; Westfall, Kyle B; Lian, Jianhui; Fraser-McKelvie, Amelia; Andrews, Brett H; Drory, Niv; Meneses-Goytia, Sofia
ABSTRACT: Chemical enrichment signatures strongly constrain galaxy formation and evolution, and a detailed understanding of abundance patterns provides clues regarding the nucleosynthetic production pathways of elements. Using integral-field spectroscopy from the MaNGA (Mapping Nearby Galaxies at Apache Point Observatory) survey, we study radial gradients of chemical element abundances in detail. We use stacked spectra out to 1  R e of 366 early-type galaxies with masses 9.9−10.8 log  M /M⊙ to probe the abundances of the elements C, N, Na, Mg, Ca, and Ti, relative to the abundance of Fe, by fitting stellar population models to a combination of Lick absorption indices. We find that C, Mg, and Ti trace each other both as a function of galaxy radius and galaxy mass. These similar C and Mg abundances within and across galaxies set a lower limit for star formation time-scales. Conversely, N and Ca are generally offset to lower abundances. The underabundance of Ca compared to Mg implies delayed enrichment of Ca through Type Ia supernovae, whereas the correlated behaviour of Ti and the lighter α elements, C and Mg, suggest contributions to Ti from Type II supernovae. We obtain shallow radial gradients in [Mg/Fe], [C/Fe], and [Ti/Fe], meaning that these inferences are independent of radius. However, we measure strong negative radial gradients for [N/Fe] and [Na/Fe], of up to −0.25 ± 0.05 and −0.29 ± 0.02 dex/ R e, respectively. These gradients become shallower with decreasing galaxy mass. We find that N and Na abundances increase more steeply with velocity dispersion within galaxies than globally, while the other elements show the same relation locally and globally. This implies that the high Na and N abundances found in massive early-type galaxies are generated by internal processes within galaxies. These are strongly correlated with the total metallicity, suggesting metallicity-dependent Na enrichment and secondary N production in massive early-type galaxies.